Kition-Bamboula IX Les cultes des Salines à Kition : étude des terres cuites d'époque classique - Maillard, Pauline (Archéologie(s), 2023)
The corpus studied in this book is a collection of four hundred terracotta figurines found at the end of the 19th century on the shores of the Salt Lake at Larnaca, in south-eastern Cyprus. Based on the archives of the period, the author reconstructs a complete and detailed catalogue of the objects and explains their origins. These representations, largely dominated by the figure of a woman enthroned wearing a high calathos headdress, shed light on all aspects of clay craftsmanship in the Cypro-Phoenician milieu. It explores local "savoir-faire" and its transmission as well as the internal organisation within the terracotta workshops. They also reveal the resourceful technical processes used by the Kitians. The study looks in detail at the ways in which iconographic types were used and integrated into ritual contexts. It highlights the presence of Aphrodite and Artemis in peri-urban cults, as well as gods of Phoenician or Egyptian origin such as Astarte, Umm, Eshmoun-Melqart and Bes. By analysing the links between the marine environment and the character of the deities, the author underlines the cultural and ritual dimension of salt and the sea in the religious landscape of Cyprus, Phoenicia and the Levant. On the whole, the study reveals the historical importance of the development of cults in the kingdom of Kition in the 4th century BC.